(untitled) (CIPEEX, 2025)
BACKGROUND: Snakebite envenomations represent a significant public health issue in Brazil, particularly in regions with extensive rural areas or unplanned urban expansion¹. The state of Goiás, in Brazil’s Central-West region, has environmental and socioeconomic conditions that contribute to these incidents. Anápolis is a strategic municipality for investigation due to its geographical position and mix of urban and rural zones, making the study of its epidemiological profile essential for identifying local patterns and developing targeted interventions¹. OBJECTIVE: To analyze the epidemiological profile of snakebite envenomations in Anápolis, focusing on time to medical care, victim’s educational level, and case outcomes. METHODS: This is an observational, descriptive, and retrospective study based on data from SINAN/DATASUS regarding snakebite accidents in Anápolis-GO (2020–2025). RESULTS: Of the snakebite cases analyzed, 43.1% of victims had completed or incomplete high school or higher education, 8.3% had completed primary education, and 39.5% had incomplete primary education (11.3% incomplete 1st–4th grade, 8.3% completed 4th grade, 19.9% incomplete 5th–8th grade). Additionally, 0.5% of cases involved illiterate individuals. Despite educational disparities, the time to seek medical care varied widely, from within 1 hour to 24 hours or more, regardless of educational level². Regarding case outcomes, of 397 reported cases, 389 (98%) resulted in recovery across all time intervals (0 to >24 hours). Three cases (0.75%) resulted in death, occurring at 0–1 hour, 6–12 hours, and after 24 hours, respectively, with 5 cases (1.25%) classified as unknown/blank³. CONCLUSION: Educational level alone does not significantly influence the time to seek medical care. Higher-educated individuals may seek care more promptly, possibly due to better access to healthcare services in urban areas, while those with lower education, often in rural areas, face greater risk exposure and access barriers4,5,6. Furthermore, the time from bite to medical care is not the primary determinant of case outcomes. Further investigation into clinical, environmental, and social factors is necessary to understand healthcare-seeking behavior and improve snakebite outcomes.